Linkages between government spending, growth, and poverty in rural India - Fan, Shenggen; Hazell, Peter B. R.; Thorat, Sukhadeo (International Food Policy Research Institute, 1999)
This research report on India addresses an important policy issue faced by policy-makers in many developing countries: how to allocate public funds more efficiently in order to achieve both growth and poverty-reduction goals in rural areas. This research is particularly important at a time when many developing countries are undergoing substantial budget cuts as part of macroeconomic reforms and adjustment. The econometric model employed in this research includes a broad range of government expenditure items. It traces their effects on productivity growth and poverty alleviation and ranks them, exploring the potential trade-offs and complementarities of the two goals. Of the various investments weighed, the report finds that investments in rural roads and agricultural research and development have the greatest impact, while government spending specifically targeted to poverty reduction such as rural development and employment pro rams have only modest effects. In the light of these results, many developing countries may want to take a second look at their policies for poverty reduction and growth. (Forward by Per Pinstrup-Andersen)